Disruptive Community: The Irish in Argentina. Readings of Rodolfo Walsh and Juan José Delaney - Glynn, Douglas M (ABEI Journal, 2018)
A community is principally characterized by the collectivity of its members and is defined spatially in terms of arbitrary boundaries that consistently separate its inhabitants from ‘Others’ and the “otherness” of the external world. For a number of centuries the diasporic Irish community has been able to forge communal spaces in Caribbean and Latin American nations, most prominently in Argentina. Nonetheless, these Irish communities in Argentine literature are often represented as insular and, therefore, disruptive to the monolithic national discourse of the host country. The portrayal of the diasporic Irish figure, which deviates from patterns of social normativity, constitutes an important facet of these individuals that permits an analysis of the ways in which their presence interrupts the Argentine literary imaginary. As Hellen Kelly observes, “‘deviancy’ in its variant forms has become, therefore, the most accessible and fruitful approach to assessing levels of integration amongst Irish immigrant communities” (128). In order to examine and comment on the various forms of deviations and, at the same time, the levels of integration of the immigrant Irish community, I offer my readings of the three short stories which comprise the “Irish series” by Rodolfo Walsh and Juan José Delaney’s novel Moira Sullivan. I look to interrogate the elements of the diasporic Irish experience which have informed and given shape to representations of diasporic Irish individuals and the spaces they occupy. I also seek to problematize previous readings of the selected texts that have, in general, omitted any critical consideration of and reflection upon their imbued ‘Irishness’ within the context of Argentine literary imaginaries.Keywords: Rodolfo Walsh; Juan José Delaney; Irishness; Irish immigration.